Em busca da credibilidade perdida: a rede de investigação jornalística na era das fake news - Santos, Kassia Nobre dos (2018)
The social networks have praised the participative culture of society regarding to subjects of collective interest, something positive because it has been promoting the diversity of voices and decentralizing the power from the mainstream media as the unique advocate of information. At the same time, the digital revolution was the responsible for post-truth also fake news, which both have disrupted the concept of truth, once opinions and facts mix each other because they are on the same digital area. In this scenario, fundamental principles due to the profession of journalism - detailed verification and check - have been rescued and valued from the begining of new ways of work. From the discussion of journalism under the perspective of its processes of production, the goal of this research is based on proposing a reflection towards the manners of acting of journalists of revista Piauí (Piauí Magazine) and agência Lupa (Lupa Agency), willing to understand the procedures which are used by them focused on the report creation as well as the check. The Piauí magazine has been in Brazilian market for over ten years and it is an example for other actual models regarding to the big report construction. The Lupa agency was the first agency of fact-checking in Brazil. The theoretical basis for this analysis are the critical theory of creative processes (Salles, 2008; 2011; 2016; 2017). The analytical tools are the “documents of processes” which are material records from creative process. For the actual research, some interviews were conducted with journalists of Piauí magazine as well as the creator of Lupa agency in order to understand their creative processes. From these datas, a journalistic research network was created containing the following analytical issues: the narrative, the transparence and the error correction. Consequently, the present thesis is based on the fact there is an experimental field to be explored by journalist in order to act toward the crisis of this profession in addition to reclaim the lost credibility. Moreover, from the combat of misinformation, the journalism is able to recover one of its main role which is the reinforcement of the democracy